Electromechanical and magnetic properties of BiFeO3-LaFeO3-CaTiO3 ceramics near the rhombohedral-orthorhombic phase boundary - Karpinsky, D. V. (2017)
BiFeO3-LaFeO3-CaTiO3 ceramics have been studied by X-ray diffraction, magnetization measurements, and piezoresponse force microscopy (PFM). The compositional ranges of the polar, antipolar, and non-polar phases have been estimated. PFM measurements testify gradual decrease of piezoelectric response in Bi(0.85-x)La(0.15)CaxFe(1-x)Ti(x)O(3) system with Ca/Ti content increase, except a narrow concentration region near polar-antipolar phase boundary where piezoelectric signal shows maximum value. It is found that increase of dopant concentration leads to apparent decrease of the off-center Bi-O displacement and, consequently, causes a reduction of piezoelectric response. It is concluded that notable remanent magnetization in polar and non-polar structural phases is a result of the Dzyaloshinsky-Moria interaction. (C) 2013 AIP Publishing LLC